Fiber-optic sensor to estimate surface roughness of corroded metals - Gobi, Govindan; Sastikumar, Dillibabu; Balaji Ganesh, Athi; Radhakrishnan, Thotta (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
A fiber optic sensor system is developed to probe the surface texture of corroded metals. The present work is based on the principle of scattering of light by objects. A light beam from an LED source is focused onto the corroded surface. Specular and diffuse reflection of the surface is measured vertically at normal incidence of a fiber. The observed response agrees well with mechanical stylus measurements, with R2 > 0.89. The fiber optic sensor system can be used to estimate the roughness of metals due to any type of corrosion without erosion. The obtained results show a consistent relationship between measured and surface roughness levels.
Optica Applicata, Vol. 39, 2009, nr 1, s. 5-11
Keywords: optyka; fiber optic sensor; scattering principle; surface roughness; corrosion